Knowledge, attitudes & practices of healthcare professionals in hospitals towards the reporting of adverse drug reactions in Saudi Arabia: A multi-centre cross sectional study - Thamir M. AlShammari; Mohammed J. Almoslem (Elsevier, 2018)
Introduction: Adverse drug reactions (ADRs) are a major global clinical problem, causing substantial mortality and morbidity especially in hospitals. Healthcare professionals (HCPs) knowledges', attitude and practices are crucial points to evaluate the hospital safety environment. Objective of the study was to investigate the knowledge, attitudes, and practices of HCPs regarding the ADRs reporting system. Methods: A cross-sectional survey was conducted between January and February of 2013 in nine tertiary care hospitals (governmental and private) that provide highly specialized medical services in Riyadh, Qassim, and the Eastern region of the Kingdom of Saudi Arabia. A validated questionnaire was used to assess the knowledge, attitudes, and practices of HCPs regarding the ADR reporting system. All statistical analyses were performed using SAS version 9.2. Results: In total, 480 questionnaires were distributed, and the response rate was 70% (n = 336). Only 33% of the participants were aware of the National Pharmacovigilance Centre (NPC). Of those HCPs who were familiar with the NPC and their responsibility to report ADRs, most (50%) were pharmacists, followed by physicians (24%) and nurses (16%), and these differences were statistically significant (p < 0.01). Twenty-seven percent of the participants were involved in reporting ADRs; among these HCPs, 62% were pharmacists, 26% were nurses, and 6% were physicians. Most participants (95%) favoured reporting ADRs caused by antibiotics and new/old drugs. The prominent factors discouraging ADR reporting included fear that the report might be incorrect (46%) and lack of time (44%). Conclusions: A significant lack of knowledge, positive attitudes, and practices regarding ADRs and reporting was observed in hospital HCPs. This finding represents an international concern, and urgent action is needed to promote drug safety and pharmacovigilance in this region. Keywords: Adverse drug reaction, Cross-sectional, Healthcare professionals, Pharmacovigilance